Benzovindiflupyr at estimated drinking water concentrations induces hepatic injury via the NF-κB signaling pathway: In vivo, in vitro, and in silico studies - Jiyan Miao; Shihang Han; Sinuo Tian; Wei Sun; Xiaoxuan Sun; Yifan Yue; Xinrui Dang; Qi Chen; Jinling Diao; Miaomiao Teng; Wentao Zhu (Environmental Pollution, 2026)

Effect of horizontal cartridges on the uniformity of flow field distribution inside a cartridge filter - Muze Han; Shihang Li; Gengjun Li; Hao Jin; Yingchao Wei (Journal of Cleaner Production, 2024)

Co-exposure to boscalid and amoxicillin inhibited the degradation of boscalid and aggravated the threat to the earthworm - Shihang Han; Wei Sun; Xiaoxuan Sun; Yifan Yue; Jiyan Miao; Xinrui Dang; Jinling Diao; Miaomiao Teng; Wentao Zhu (Pesticide Biochemistry and Physiology, 2024)

Geochemical behavior of C, N, and S in sediments of Hangzhou Bay, Southeastern China: implications for the study of paleoclimate and sea-level changes - Qin Gao; Alexander M. Piotrowski; Zilong Li; Pei Sun Loh; Cuicui Han; Zixuan Wang; Shihang Yang; Zengqing Guo; Dongqin Huang; Yanting Chen (Frontiers in Marine Science, 2024)
The correlation between the amount of organic carbon (OC) and sulfur (S) in sediments has been widely used as a paleosalinity indicator to distinguish between marine and freshwater environments. However, whether the ratio of total OC to total S (TOC/TS) can be used to identify unsteady or dynamic marine environments across sedimentary strata is still contended. An HZW1907 sediment core of 80 m in length was successfully collected in the middle of Hangzhou Bay (HZB), serving as one of the few boreholes that are crucial for the study of geologic and geo-environment changes in the coastal regions of eastern China since the Last Glacial Maximum (LGM). Total OC (TOC), stable carbon isotope, and TS of 82 subsamples from the HZW1907 core were analyzed to reconstruct the history of the shallow water biological pump and sulfur preservation record in the bay since the Late Pleistocene. Our results indicate that the samples had low concentrations of TOC (0.21%) and total nitrogen (TN) (0.02%), high mass ratio of TOC/TN (10.8), low δ 13 C (−24.9‰), low TS content (0.06%), and a high ratio of TOC/TS (9.1) from 33.6 ka BP to 12.3 ka BP, implying that freshwater organic matter (OM), algae, and C3 plant fragments were the main sources of OM in a relatively cold environment. The abundances of TOC, TN, and TS increased to 0.56%, 0.07%, and 0.4%, respectively, while δ 13 C (−23.9‰) increased and TOC/TS (2.7) decreased in the Holocene sediments, suggesting that seawater began to influence the composition of the sediments of HZB. Climate warming, which is likely to have impacted the results, was experienced from 12.3 ka BP. An OC isotope mixing model indicated that since the Mid-late Holocene, more than 70% of riverine OM accounted for the total OM. The TOC/TS ratio was identified as an effective indicator of seawater intrusion, with C/S ratios of 1–6 being considered to indicate a “sea–land transitional zone” sedimentary environment, a C/S >6 indicating freshwater, and a C/S<1 indicating normal marine facies. These findings provide crucial evidence for using TOC/TS to distinguish freshwater from marine environments and enhance our understanding of past climate changes. Therefore, these geochemical indicators can be used in conjunction with other sedimentary records to obtain accurate results about sedimentary evolution.

Bifidobacterium mediate gut microbiota-remedied intestinal barrier damage caused by cyproconazole in zebrafish (Danio rerio) - Xiaoxuan Sun; Sinuo Tian; Sen Yan; Wei Sun; Jiyan Miao; Yifan Yue; Shihang Han; Shiran Huang; Ning Xu; Jinling Diao; Zhiqiang Zhou; Wentao Zhu (Science of The Total Environment, 2024)

Global fast terminal sliding mode control for path following of ultra large underactuated ship based on predictive LOS guidance - Hugan Zhang; Xianku Zhang; Shihang Gao; Xu Han; DaoCheng Ma (Ocean Engineering, 2023)

Effects of filter cartridge wetted before filtration and during filtration on the performance of cartridge dust collector - Shihang Li; Liyuan Liu; Xiaoyu Tan; Hao Liu; Changgeng Gui; Xingyue Chen; Muze Han; Yihan Lin; Jiang Shao; Liang Yuan; Fubao Zhou (Process Safety and Environmental Protection, 2023)

Bioelectret poly(lactic acid) membranes with simultaneously enhanced physical interception and electrostatic adsorption of airborne PM0.3 - Han Shang; Keke Xu; Tian Li; Hao-Ran Yang; Jiefeng Gao; Shihang Li; Jintuo Zhu; Xinjian He; Shenghui Zhang; Huan Xu; Baolong Shen (Journal of Hazardous Materials, 2023)

Research and application of self-powered induction spray dust removal system for long-distance belt conveying in underground coal mines - Jun Hou; Shihang Li; Shuda Hu; Hui Cheng; Muze Han; Changgeng Gui; Qiaosong Guo; Liang Yuan; Fubao Zhou (Process Safety and Environmental Protection, 2023)

A new strategy to alleviate the obesity induced by endocrine disruptors—A unique lysine metabolic pathway of nanoselenium Siraitia grosvenorii to repair gut microbiota and resist obesity - Yu Wang; Wei Sun; Sen Yan; Zhiyuan Meng; Ming Jia; Sinuo Tian; Shiran Huang; Xiaoxuan Sun; Shihang Han; Canping Pan; Jinling Diao; Qiuxia Wang; et al. (Food and Chemical Toxicology, 2023)

Residue Behavior and Risk Assessment of Pyraclostrobin and Thifluzamide in Cowpea - Shihang Han; Yingying Bi; Lijun Han; Shuangyu Song; Ziyu Ye; Fayi Qin; Xinru Lv (Bulletin of Environmental Contamination and Toxicology, 2022)